Social interaction in virtual environment (virtual environment / 3D animation ) - Zatil Alyani, binti Hanifah (University Malaysia Sarawak, UNIMAS., 2006)
This project aims to study and designs a rich Virtual Environment (VE), which allows social interaction between object in the environment. The specific objectives of this project are to (1) study about social interaction in Virtual Environment, (2) develop a VE and add some animations to the objects especially human embodiments (3) model a realistic, detailed and convincing body animation and (4) apply the social interaction in VE as an entertainment. This includes development of human embodiment with some animation added. A PC-based software package from Discreet: 3D Studio Max 7.0 is used for completing this project. The process of developing is broken down into four phases; the preproduction phase, first production phase which is building and texturing, second production phase or called animating and the postproduction phase. The result is animations consist of 3-5 minutes interaction. The analysis of end result shows the implication of the project and description of the strength and its weaknesses. This project also has given several recommendations on how to improve the future project.